Introduction to quantum mechanics in chemistry, materials science and biology - Blinder S M (Amsterdam Elsevier, 2004)
This book provides a lucid, up-to-date introduction to the principles of quantum mechanics at the level of undergraduates and first-year graduate students in chemistry, materials science, biology and related fields. It shows how the fundamental concepts
Keywords: Quantum biochemistry; Quantum chemistry; Quantum theory